Effect of post-treatment on the microstructure and mechanical properties of selective laser melted Ti6Al4V lattice structures. Issue 9 (7th August 2020) - Huang, Xina; Lang, Lihui; Gong, Shuili; Zhao, Mali
Abstract : Purpose: The purpose of this paper is to investigate the post-treatment processes on lattice structures of selective laser melting. Moreover, the effect of pressure during hot isostatic pressing (HIP) is determined. Design/methodology/approach: Three post-treatment processes, annealing at 650°C, 920°C and HIP were adopted. The microstructure evolution and mechanical properties of selective lasering melted Ti6Al4V lattice structures after post-treatment were systematically investigated by optical microscope, scanning electron microscope, electron backscattered diffraction, differential scanning calorimetry and quasi-static mechanics tests. Findings: The main findings in this paper are as below: first, the pores existing in the samples as-fabricated, annealed at 650°C and 920°C are disappeared after HIP. Second, the microstructure and compressive properties after HIP are similar to that after pure annealing at the same temperature. However, the HIPed sample had the highest number of cycles to failure. Third, the fracture mechanism of as-fabricated samples changes from mixed fracture to the micro-voids accumulation fracture after post-treatment processes. Originality/value: HIP post-treatment can be replaced by annealing at the same temperature when the requirement for porosity and fatigue life is not very high.